In Vitro Cytotoxic Study for Purified Resveratrol Extracted from Grape Skin Fruit Vitis vinifera - Y. Mohammed, Zainab; F. Al-Jumaily, Essam; Y. Yaseen, Nahi (Iraqi Journal of Pharmaceutical Sciences, 2017)
This study was conducted with the aim to extract and purify a polyphenolic compound â€œ Resveratrolâ€ from the skin of black grapes Vitis vinifera cultivated in Iraq. The purified resveratrol is obtained after ethanolic extraction with 80% v/v solution for fresh grape skin, followed by acid hydrolysis with 10% HCl solution then the aglycon moiety was taken with organic solvent ( chloroform). Using silica gel G60 packed glass column chromatography with mobile phase benzene: methanol: acetic acid 20:4:1 a partial purified resveratrol was obtained then preperative thin layer chromatography technique yielded pure crystals identified as resveratrol (mixture of two isomers cis and trans) in relation to resveratrol standard (35 mg resveratrol crystals / 0.5 kg fresh grape skin was obtained as a result of these processes ). The study was also employed an in vitro evaluation the cytotoxic effect of pure resveratrol on some cell line including : the murine mammary adenocarcinoma AMN-3 cell line, the human laryngeal carcinoma (Hep-2) cell line and the Rat embryo fibroblast (Ref) cell line, at different concentrations and different expousure time. The cytotoxic effect of the pure resveratrol was studied in comparison with trans- resveratrol standard in concentrations of (12.5, 25, 50 and 100) Âµg/ml for both purified resveratrol and the standard, also the comparism included methotrexate drug in concentrations (0.05 , 0.1 , 0.2 and 0.4) Âµg/ml toward the growth effects of the three types of cell lines and at three exposure times (24, 48 and 72) hours. The cytotoxic inhibition effect for the purified extracted resveratrol revealed that the highest significant effect (P<0.01) was achieved after 24 hr of exposure on both AMN-3 and Ref cell lines. Hep-2 cell line responded to extracted resveratrol in different manners. Keywords: Resveratrol , grape skin , polyphenols, cytotoxic study